Discovery of novel [FeFe]-hydrogenases for biocatalytic H2-production. Issue 43 (30th September 2019) - Land, Henrik; Ceccaldi, Pierre; Mészáros, Lívia S.; Lorenzi, Marco; Redman, Holly J.; Senger, Moritz; Stripp, Sven T.; Berggren, Gustav
Abstract : A semi-synthetic screening method for mining the biodiversity of [FeFe]-hydrogenases, expanding the toolbox for biocatalytic H2 -gas production. Abstract : A new screening method for [FeFe]-hydrogenases is described, circumventing the need for specialized expression conditions as well as protein purification for initial characterization. [FeFe]-hydrogenases catalyze the formation and oxidation of molecular hydrogen at rates exceeding 10 3 s −1, making them highly promising for biotechnological applications. However, the discovery of novel [FeFe]-hydrogenases is slow due to their oxygen sensitivity and dependency on a structurally unique cofactor, complicating protein expression and purification. Consequently, only a very limited number have been characterized, hampering their implementation. With the purpose of increasing the throughput of [FeFe]-hydrogenase discovery, we have developed a screening method that allows for rapid identification of novel [FeFe]-hydrogenases as well as their characterization with regards to activity (activity assays and protein film electrochemistry) and spectroscopic properties (electron paramagnetic resonance and Fourier transform infrared spectroscopy). The method is based on in vivo artificial maturation of [FeFe]-hydrogenases in Escherichia coli and all procedures are performed on either whole cells or non-purified cell lysates, thereby circumventing extensive protein purification. The screening was applied on eight putative [FeFe]-hydrogenases originating from different structural sub-classes and resulted in the discovery of two new active [FeFe]-hydrogenases. The [FeFe]-hydrogenase from Solobacterium moorei shows high H2 -gas production activity, while the enzyme from Thermoanaerobacter mathranii represents a hitherto uncharacterized [FeFe]-hydrogenase sub-class. This latter enzyme is a putative sensory hydrogenase and our in vivo spectroscopy study reveals distinct differences compared to the well established H2 producing HydA1 hydrogenase from Chlamydomonas reinhardtii .